BRUSH DRIVE SYSTEM OF AERODROME SWEEPER WITH HYDROMOTOR THROTTLE SYNCHRONIZATION - Alexander T. Rybak; Alexander I. Martynenko; Mikhail V. Ustyantsev (Advanced Engineering Research, 2011)
A mathematical model that enables to pursue a theoretical study on the brush drive system of the aerodrome sweeper fitted with the synchronous hydraulic system based on the membranous throttle flow divider is offered.